Identification of Paracetamol in Jamu Using Thin Layer Chromatography Analysis Method - Iga Yastiara; Fajar Nugraha; Hadi Kurniawan (Journal Syifa Sciences and Clinical Research, 2022)
Jamu is one of the Indonesian traditional medicine. Jamu is efficacious for health so it is widely consumed by the society. The high level of consumption causes trade competition from jamu industry in various regions, including in Pontianak City, West Kalimantan. However, several jamu industries in Pontianak have violated the law by adding medicinal chemicals to jamu. The most widely added medicinal chemical in jamu is paracetamol. Paracetamol which indicates as an analgesic-antipyretic can be harmful for health because it increases liver hepatotoxicity if consumed continuously.This study aims to identify paracetamol in herbal medicine. A total of 10 samples were obtained in Pontianak City, West Kalimantan by purchasing directly or from an online shop. This study used thin layer chromatography as an instrument of qualitative analysis. The results of the analysis using thin layer chromatography were Rf samples A, B, and G were 0.675, respectively; 0.6625; 0.6625 which is close to the standard Rf value for comparison of paracetamol, which is 0.675. Those three samples contained paracetamol because they had a different Rf value 0.05 from the standard Rf value.